Hubungan Gaya Hidup dengan Kejadian Gout Arthritis di Desa Meunasah Papeun Kecamatan Krueng Barona Jaya Kabupaten Aceh Besar - Defri Mahendra; Yadi Putra; Irma Andriani (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2025)
Gout arthritis is a metabolic disorder characterized by excessive uric acid levels in the blood, namely more than 7 mg/dl in men and more than 6 mg/dl in women. Gout arthritis can occur in all age groups, both young and old, in men and women, with its prevalence ranking second after hypertension in the community. The purpose of this study was to determine the relationship between lifestyle and the incidence of gout arthritis in Meunasah Papeun Village, Krueng Barona Jaya Subdistrict, Aceh Besar District in 2025. This research used an analytic design with a cross-sectional approach and a total sample of 41 people with high uric acid levels in Meunasah Papeun Village, Krueng Barona Jaya Subdistrict, Aceh Besar District in 2025. The sampling technique applied in this study was total sampling. The research was conducted from April 6 to April 16, 2025, and the data were analyzed using univariate and bivariate analysis with the Chi-Square test. The results showed that of the 22 respondents with a good lifestyle, most did not experience gout arthritis (81.8%), while of the 19 respondents with a poor lifestyle, the majority experienced gout arthritis (68.4%). The Chi-Square test obtained a p-value of 0.003 < 0.05, indicating a significant relationship between lifestyle and gout arthritis. In conclusion, there is a significant relationship between lifestyle and gout arthritis. It is suggested that the research site increase public knowledge about gout arthritis, especially for those who suffer from the disease, by providing health education on healthy lifestyle practices and conducting regular health check-ups.